Penguatan Islam Moderat di Era Disrupsi - Muniroh, Alimul (Proceedings of Annual Conference for Muslim Scholars, 2022)
There were two points that moderate Islamic groups face when coexisting with the millennial generation in Indonesia. The first was the strengthening of radical militant groups, and the second was the emergence of the era of disruption. Changes in the pattern of movement patterns from radical militant groups had become a separate dynamic for socio-political discourse in Indonesia. Meanwhile, the era of disruption was like a demand and necessity for the millennial generation, so that both radical militant groups and moderate Islamic groups must be good at playing a role in this era of disruption. This paper explains how to strengthen moderate Islam in the millennial generation in Indonesia.